1991
DOI: 10.3758/bf03212215
|View full text |Cite
|
Sign up to set email alerts
|

Memory for objects and parts

Abstract: Performance on whole comparisons of two whole objects was compared to that for partial comparisons of a whole object and a part. In particular, same-different comparisons were measured for sequential displays of two-dimensional line figures. The comparisons were analogous to those in the word priority paradigm (Johnson, 1975). The whole comparisons were found to be more accurate and faster than the partial comparisons. This whole advantage was also found for accuracy using a two-alternative forced-choice proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
1
11
0
1
Order By: Relevance
“…This possibility could potentially undermine the generality of the current results and those of other studies showing part-based effects in whole-part matching tasks (e.g., Ankrum & Palmer, 1991;Palmer, 1977). The objection is unsatisfactory for a number of reasons.…”
Section: Methodological Issuesmentioning
confidence: 61%
“…This possibility could potentially undermine the generality of the current results and those of other studies showing part-based effects in whole-part matching tasks (e.g., Ankrum & Palmer, 1991;Palmer, 1977). The objection is unsatisfactory for a number of reasons.…”
Section: Methodological Issuesmentioning
confidence: 61%
“…Experiments 2a and 2b were conducted to examine effects of stimulus dimensionality and connectivity on color change detection while controlling for other stimulus properties. Based on the previous research showing an advantage for 3D stimuli (Ankrum & Palmer, 1991 ; Lanze, et al, 1982 , 1985 ; Purcell & Stewart, 1991 ; Weisstein & Harris, 1974 ), we tested the hypothesis that change detection would be enhanced for 3D objects ( dimensionality hypothesis).…”
Section: Methodsmentioning
confidence: 99%
“…Object dimensionality refers to the more traditional meaning of dimensionality; that is, the number of dimensions each stimulus unit has (e.g., 2D shapes vs. 3D geons). While dimensionality is irrelevant to a color change, a history of visual cognition has shown that 3D object-like stimuli are easier to perceive (Purcell & Stewart, 1991 ) and also enhance perception (Lanze, et al, 1982 , 1985 ; Weisstein & Harris, 1974 ) and memory (Ankrum & Palmer, 1991 ) for line-drawn stimuli. Moreover, color change detection can be enhanced by including depth information in stereoscopic displays, when isolated colored squares are shown in different depth planes (Chunharas et al, 2019 ; Sarno et al, 2019 ; Xu & Nakayama, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the mental synthesis task (Palmer, 1977, experiment III ; see also Ankrum & Palmer, 1991), comparisons of simple geometrical figures are used to assess holistic effects on segmentation and groupings. Holistic properties emerge only with the processing of all the parts and dimensions of a stimulus (Kimchi, 1992).…”
Section: Experiments 2 : Mental Synthesismentioning
confidence: 99%